Mechanical testing and modelling of the Universal 2 implant. Issue 6 (June 2016) - Gislason, M.K.; Foster, E.; Main, D.; Fusiek, G.; Niewczas, P.; Bransby-Zachary, M.; Nash, D.H.
Highlights: Validation of a finite element model of a total wrist implant. Novel measuring method to use Fibre Bragg Grating in conjunction with strain gauges. Quantified the strains acting on wrist implants during high load cases. Abstract: Understanding the load mechanics of orthopaedic implants is important to be able to predict their behaviour in-vivo. Much research, both mechanical and clinical, has been carried out on hip and knee implants, but less has been written about the mechanics of wrist implants. In this paper, the load mechanics of the Universal 2 wrist implant have been measured using two types of measuring techniques, strain gauges and Fibre Bragg Grating measurements to measure strains. The results were compared to a finite element model of the implant. The results showed that the computational results were in good agreement with the experimental results. Better understanding of the load mechanics of wrist implants, using models and experimental results can catalyse the development of future generation implants.